Impact of Prostate Urethral Lift Device on Prostate Magnetic Resonance Image Quality. Issue 4 (11th April 2023) - Benidir, Tarik; Austhof, Ethan; Ward, Ryan D.; Ream, Justin; Bullen, Jenifer; Turkbey, Baris; Pinto, Peter A.; Giganti, Francesco; Klein, Eric A.; Purysko, Andrei S.
Abstract : Purpose: Prostatic urethral lift with UroLift is a minimally invasive approach to treat symptomatic benign prostatic hypertrophy. This device causes artifacts on prostate magnetic resonance images. Our aim was to evaluate the impact of artifact on prostate magnetic resonance image quality. Materials and Methods: This was a single-center retrospective review of patients with UroLift who subsequently had prostate magnetic resonance imaging. Two readers graded UroLift artifact on each pulse sequence using a 5-point scale (1—nondiagnostic; 5—no artifact). Prostate Imaging Quality scores were assigned for the whole data set. The volume of gland obscured by artifact was measured. Linear and logistic regression models were used to identify predictors of poor image quality. Results: Thirty-seven patients were included. Poor image quality occurs more in the transition zone than the peripheral zone (15% vs 3%), at base/mid regions vs the apex (13%, 9%, and 5%, respectively) and on diffusion-weighted images vs T2-weighted and dynamic contrast-enhanced sequences (27%, 0.3%, 0%, respectively; P < .001). Suboptimal image quality (ie, Prostate Imaging Quality score ≤2) was found in 16%-24% of exams. The percentage of gland obscured by the UroLift artifact was higher on diffusion-weighted images and dynamic contrast-enhanced sequences than T2-weighted (32%, 9%, and 6%, respectively; P < .001). Conclusions: UroLift artifact negatively affects prostate magnetic resonance image quality with greater impact in the mid-basal transition zone, obscuring a third of the gland on diffusion-weighted images. Patients considering this procedure should be counseled on the impact of this device on image quality and its potential implications for any image-guided prostate cancer workup.